PENGARUH EARNING PER SHARE DAN DEBT TO EQUITY RATIO T ERHADAP RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Perbankan Konvensional Yang Terdaftar Di BEI Periode 2018-2020) - An am, Lutfi Chairul; Sari, Lita Permata; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
The company is an organizational body that has an important role in the economic development of a country, especially for investors. The purpose of this study was to analyze and test the effect of EPS, DER on stock returns with dividend policy as an intervening variable. The population in this study are banking companies listed on the Indonesia Stock Exchange for the period 2018-2020. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that EPS has a significant effect on dividend policy, DER has a significant effect on dividend policy, EPS has a significant effect on stock returns, DER has a significant effect on stock returns, dividend policy has a significant effect on stock returns. The results of the indirect effect hypothesis test show that the EPS variable on stock returns through dividend policy has a significant positive effect, DER on stock returns through dividend policy has a significant negative effect.